The Role of Academic Achievement and Parental Involvement in Improving Student Subjective Well-Being - Sekar Wangi; Asri Mutiara Putri; Supriyati; Syafik Arisandi (Faculty of Psychology, Universitas Semarang, 2025)
This study analyzes the influence of academic achievement and parental involvement on student subjective well-being (SSWB) among high school students in Bandar Lampung City. SSWB encompasses students' perceptions of the quality of life at school, including school connectedness, academic success, enjoyment of learning, and educational goals. This study used a quantitative approach, with 200 students from two private high schools as a sample selected through quota sampling. The instruments used included the SSWQ scale, a parental involvement scale, and report card data as an indicator of academic achievement. The results showed that academic achievement and parental involvement significantly influenced SSWB, both partially and simultaneously, with parental involvement having a greater influence (β = 0.464; effective contribution = 22.41%) than academic achievement (β = 0.296; effective contribution = 9.65%), with an R Square of 0.320. These findings confirm the importance of parents' roles and academic achievement in supporting students' subjective well-being at school.